Zonas de liberdade LGBTI+? Práticas e gramáticas para uma intervenção profissional inclusiva com crianças e jovens LGBTI+ - Esteves, M.; Santos, AC; Alexandra Santos (Ex Aequo, 2021)
LGBTI+ Freedom Zones? Practices and grammars for an inclusive professional intervention with LGBTI+ children and young people Drawing on findings from the European research project «Diversity and Childhood», whose qualitative and quantitative methodology involved children, young people and professionals from areas such as education, health and family intervention, in this paper the authors identify good practices as affirmative action measures in LGBTI+ mainstreaming, but also gaps and resistances that affect the daily lives of LGBTI+ children and young people. Understanding the perspectives of the different actors involved is a fundamental step to adjust the implementation, monitoring and application of laws and measures that aim to guarantee equality and non-discrimination based on sexual orientation, gender identity and expression and sexual characteristics.